Finite Element Method Simulation, Numerical Analysis and Solution Techniques - Păcurar, Răzvan (IntechOpen, 2018)
The book entitled Finite Element Method: Simulation, Numerical Analysis, and Solution Techniques aims to present results of the applicative research performed using FEM in various engineering fields by researchers affiliated to well-known universities. The book has a profound interdisciplinary character and is mainly addressed to researchers, PhD students, graduate and undergraduate students, teachers, engineers, as well as all other readers interested in the engineering applications of FEM. I am confident that readers will find information and challenging topics of high academic and scientific level, which will encourage them to enhance their knowledge in this engineering domain having a continuous expansion. The applications presented in this book cover a broad spectrum of finite element applications starting from mechanical, electrical, or energy production and finishing with the successful simulation of severe meteorological phenomena.